ANDROGEN PRODUCING TUMOUR: UTILISING OVARIAN AND ADRENAL VENOUS SAMPLING - Ew, Nur Aini; Kg, Goh; N, Azraai B (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Androgen-secreting tumour (AST) is rare, with a prevalence of 0.2% among women with hirsutism. Ovarian and adrenal venous sampling (OAVS) is useful in localising the tumour but has low success rate. We reported a case of ovarian AST with successful cannulation of all 4 veins. RESULTS A 26-year-old woman presented with secondary amenorrhoea, hirsutism and voice deepening for 5 years. She did not have Cushing syndrome, or manifestations related to hyperprolactinemia or congenital adrenal hyperplasia. Her family history was unremarkable. On examination, blood pressure was 112/75 mmHg, heart rate 82/min, weight 73 kg, and BMI 25.8 kg/m2 . She has a feminine body habitus with Ferriman-Gallwey score of 17. She has no clitoromegaly. Serum testosterone was 14x the upper limit of normal at 28.87 nmol/L. The following serum hormonal tests were all within normal: TSH 1.194 mU/L, fT4 12.0 pmol/L (7-14.4), prolactin 310 µU/mL, LH 5.8 mU/mL, FSH 6.8 mU/mL, oestradiol 247 pmol/L, Dehydroepiandrostenedione-sulphate (DHEAS) 5.9 µmol/L. Free androgen index was 48 (4x ULN for female). AST of the ovary was suspected. MRI of the adrenal glands and pelvis revealed a heterogeneous enhancement of the left ovary, slightly larger than the right, and normal adrenal glands. All 4 veins were successfully cannulated during OAVS. The increased testosterone secretion was lateralised to the left ovary, consistent with the MRI, with lateralization ratio of 7.9 and 4.4. DISCUSSION A very high testosterone level should raise suspicion of AST. Testosterone >3 nmol/L has a sensitivity of 100% and specificity of 53% in detecting AST. Some reported values >5.2 nmol/L with convincing history. DHEAS level of >18.9 mmol/L strongly suggests adrenal origin. OAVS is useful in cases of small ovarian AST that could not be excluded from biochemical and imaging studies. However, it is a difficult and highly demanding procedure. A centralto-peripheral oestradiol ratio of >2 confirms successful ovarian vein catheterisation. An ovarian vein testosterone gradient of >1.44 confirms lateralization (1). CONCLUSION A very high serum testosterone should raise suspicion of AST. OAVS, although difficult, is useful in localising the tumour.